Book Reviews. (1st September 2018) - Jontes, Dejan; Halskov, Andreas; Samuels, Rob
Para-Interactivity and the Appeal of Television in the Digital Age, Oranit Klein Shagrir (2017)London: Lexington Books, 111 pp., ISBN: 978-1-49854-080-3, h/bk, £54.95TV Outside the Box: Trailblazing in the Digital Television Revolution, Neil Landau (2016)New York: Focal Press, 456 pp., ISBN: 978-1-31743-971-4, p/bk, £24.00h/bk, £91.72Television 2.0: Viewer and Fan Engagement with Digital TV, Rhiannon Bury (2018)New York: Peter Lang, 147 pp., ISBN: 978-1-43313-852-2, p/bk, 47.95